Buddenbrooks: Verfall einer Familie - Mann, Thomas 1875-1955 (Frankfurt am Main Fischer, 1960)
Buddenbrooks chronicles the decline of a wealthy north German merchant family over the course of four generations, incidentally portraying the manner of life and mores of the Hanseatic bourgeoisie in the years from 1835 to 1877. Mann drew deeply from the history of his own family, the Mann family of Lübeck, and their milieu.
Paul Thomas Mann (1875-1955) was a German novelist, short story writer, social critic, philanthropist, essayist, and the 1929 Nobel Prize in Literature laureate. His highly symbolic and ironic epic novels and novellas are noted for their insight into the psychology of the artist and the intellectual.
It was Mann's first novel, published when he was twenty-six years old in 1901. With the publication of the second edition in 1903, Buddenbrooks became a major literary success.
Keywords: 20th Century (1901-2000); Literature; Novel